Siri" Na Pacce in Tax Compliance: An Ethnographic Study of The Bugis-Makassar Community - Masrullah; Alimuddin; Darwis Said; Amir (Poltanesa, 2025)
This study explores how the cultural values of Siri’ na Pacce shape tax compliance behavior within the Bugis-Makassar community by employing a qualitative ethnographic approach. Data were collected through participatory observation, in-depth interviews with taxpayers, MSME owners, community leaders, and tax officials, as well as analysis of socio-cultural documents in Makassar City. The findings reveal that Siri’, which embodies shame, honor, and personal dignity, functions as an internal moral regulator that encourages individuals to act honestly and responsibly in fulfilling their tax obligations. Conversely, Pacce, which reflects empathy and social solidarity, fosters the understanding that taxation is a collective contribution to public welfare. The interaction between these cultural values generates two forms of compliance: value-based voluntary compliance driven by internal moral awareness, and community norm–based social compliance reinforced by social pressure, reputation, and collective expectations. The study demonstrates that Siri’ na Pacce not only shapes personal behavior but also forms social norms and community-based monitoring that strengthen collective commitment to tax compliance. These values act as social capital, enhancing public trust in tax authorities and supporting voluntary compliance beyond legal enforcement. The findings further indicate that cultural-based communication strategies used by tax officials increase public receptiveness and legitimacy of tax policies. This study concludes that integrating local cultural values into tax education and outreach programs can effectively promote sustainable moral-based compliance and strengthen fiscal governance, particularly in Eastern Indonesia where Siri’ na Pacce remains deeply embedded in social identity.